STRATEGIC ANALYSIS OF INTERNAL AND EXTERNAL ENVIRONMENTS IN IMPROVING COMPETITIVENESS AND BUSINESS SUSTAINABILITY IN THE TANGGULANGIN BAG CRAFT SME IN SIDOARJO - Erfina Rochmawati; Hadiah Fitriyah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze internal and external environmental strategies in improving competitiveness and business sustainability in a Tanggulangin bag craft SME, specifically NWL (NAWAL), and to explain the managerial implications of the findings from an accounting perspective. The study focuses on internal factors, including working capital, human resources, production technology, marketing, competition, and product innovation, as well as external factors that affect the firm’s ability to survive and grow. Method: This research employed a qualitative descriptive method with a case study approach. Informants were selected purposively using the key informant technique, consisting of the business owner, production supervisor, and field foreman, because they have direct knowledge of production processes, operations, and managerial decision-making. Data were collected through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing/verification. Data validity was strengthened through source and technique triangulation. Results: The results indicate that the sustainability of NWL (NAWAL) is strongly influenced by working capital stability, experienced human resources, the use of production technology, effective digital marketing, and continuous product innovation. Limited working capital may delay raw material purchases and disrupt production schedules. The use of industrial machines improves efficiency; however, some finishing processes remain manual, and machine breakdowns may generate additional costs. In a highly competitive market, the company needs to maintain product quality while calculating the cost of goods manufactured (COGM) for each bag model more carefully so that selling prices remain competitive without reducing profit margins. Novelty: The study implies that improving SME competitiveness should be supported by stronger management accounting practices, such as transaction recording, cash flow control, cost analysis, margin evaluation, and periodic financial and non-financial performance measurement (productivity, on-time delivery, defect rates, and repeat orders).